Constitutional and legal aspects of protection of human and civil rights and freedoms in the Republic of Kazakhstan - Junussova, М.Т. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The study examines the historical development and stages of formation of the institutional framework regulating the provision of rights and freedoms of citizens on the territory of the Republic of Kazakhstan. A critical assessment of the expanding range of citizens' rights to access constitutional review is offered, while emphasizing the expansion of tools vital to the protection of inalienable human rights and freedoms. An assessment is made of the expansion of the rights and freedoms of citizens in the context of the Basic Law, ensuring their compliance with constitutional principles and studying the mechanisms and institutions responsible for ensuring compliance with these constitutional provisions. This is about assessing how these controls function to ensure the protection of the rights and freedoms of citizens within the legal and constitutional structure of the Republic of Kazakhstan. The study also aims to provide a comprehensive analysis of the implementation and practical application of constitutional review mechanisms, highlighting their effectiveness in bringing legal guarantees in accordance with the Constitution of the Republic of Kazakhstan. Methodologically, the study is based on careful observation of the prevailing situation in the field of protection of the rights and freedoms of citizens. Through this analysis, the study concludes with the presentation of pragmatic tools aimed at strengthening protective mechanisms designed to improve the effectiveness of the human rights protection system in the Republic of Kazakhstan. The proposed tools are aimed at strengthening the existing system for protecting the rights and freedoms of citizens, which will significantly increase the effectiveness and inclusiveness of human rights mechanisms, providing a comprehensive and flexible structure within the legal and constitutional paradigms of Kazakhstan.